PEGAWASAN OPERASIONAL GELANGGANG PERMAINAN DI KOTA PEKANBARU - Joni Arini Muliadi; Enawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
To overcome the issue of public entertainment in the city of Pekanbaru, the Pekanbaru city government took a concrete step by issuing one of the policies governing entertainment in the city of Pekanbaru, namely Regional Regulation Number 3 of 2002 concerning General Entertainment in the City of Pekanbaru. One of them is the game arena. This regulation aims to limit the playing field, so that in carrying out its business activities it does not harm, harm, and disturb the community, especially the surrounding environment. Based on the research that the authors did in the field, there are still playing fields that do not comply with the Regional Regulations that have been made by the Pekanbaru City Government. The purpose of this study was to find out how the operational supervision of the playing field in the city of Pekanbaru and to find out the inhibiting factors that affect the supervision.This research was conducted in the city of Pekanbaru by using a qualitative descriptive method, the data were collected through observation and interviews. This research was carried out using the Manullang theory, which set standards, made judgments, and made corrective actions.The conclusion of this research is that the supervision carried out by the Pekanbaru City Civil Service Police Unit has not been carried out effectively, this is based on the fact that there are still many playing fields that violate the regulations made by the Pekanbaru City government. This happens because the efforts made in the supervision process are not optimal in terms of human resources, sanctions, and awareness of the business owner itself.Keywords: Arena Games, Operations, Supervision